2015
DOI: 10.1111/bjh.13614
|View full text |Cite
|
Sign up to set email alerts
|

Similar outcome of upfront‐unrelated and matched sibling stem cell transplantation in idiopathic paediatric aplastic anaemia. A study on behalf of the UK Paediatric BMT Working Party, Paediatric Diseases Working Party and Severe Aplastic Anaemia Working Party of EBMT

Abstract: SummaryWe explored the feasibility of unrelated donor haematopoietic stem cell transplant (HSCT) upfront without prior immunosuppressive therapy (IST) in paediatric idiopathic severe aplastic anaemia (SAA). This cohort was then compared to matched historical controls who had undergone first-line therapy with a matched sibling/family donor (MSD) HSCT (n = 87) or IST with horse antithymocyte globulin and ciclosporin (n = 58) or second-line therapy with unrelated donor HSCT post-failed IST (n = 24). The 2-year ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
132
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 25 publications
8
132
0
3
Order By: Relevance
“…Similar to observations by Dufour et al (2015b), complications and morbidity post-transplant were minimal. Overall failure rate post-IST was 67%, with prolonged cytopenias and only partial remissions.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Similar to observations by Dufour et al (2015b), complications and morbidity post-transplant were minimal. Overall failure rate post-IST was 67%, with prolonged cytopenias and only partial remissions.…”
supporting
confidence: 85%
“…These findings prompted a study of MUD BMT as first line therapy in a UK cohort of 29 children with idiopathic SAA who lacked a matched sibling donor (Dufour et al, 2015b). Compared to historical matched controls, upfront MUD BMT was demonstrated to have superior results to first line IST and to MUD BMT performed following failure of IST, with a similar OS (96% vs. 91%) and 2-year EFS (92% vs. 87%) as SIB BMT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover, excellent UD allo-HSCT results were reported in children receiving in vivo T-cell depletion as part of their conditioning regimen, in the setting of both IST failure 8 and up-front treatment. 9 Together, these recent results suggest considering early UD allo-HSCT as a preferred option for younger patients who lack HLA-identical siblings, provided the graft be performed early after diagnosis. However, although the age limit for this procedure, the timing of UD allo-HSCT and the impact of HLA mismatch have been tested as singular factors, the combined effect of these variables during the natural history of the disease remains unclear.…”
Section: Introductionmentioning
confidence: 91%
“…In particular, young patients with disease duration of <1 year have achieved better results than adults did [40]. The EBMT group demonstrated that upfront matched or mismatched unrelated donor HSCT has similar outcomes to matched sibling donor HSCT in idiopathic severe AA of childhood and adolescence [41]. Further, a Japanese study found no differences in OS and FFS between matched sibling donor and unrelated donor HSCT [42].…”
Section: Future Directionsmentioning
confidence: 99%